Sexually transmitted infections in persons living with HIV infection and estimated HIV transmission risk: trends over time from the DC Cohort. (6th January 2020) - Secco, Alessandra Anna; Akselrod, Hana; Czeresnia, Jonathan; Levy, Matthew; Byrne, Morgan; Monroe, Anne; Lucar, Jose; Horberg, Michael; Castel, Amanda Derryck; Doshi, Rupali; Rivasplata, Heather; Squires, Leah; et al.
Abstract : Objective: A rise in incidence of STIs has been noted in the USA and in the District of Columbia (DC). We aim to describe changes in incident STIs among persons in care for HIV in Washington, DC as well as trends in HIV viral load among those with incident STIs. Methods: We conducted a retrospective DC Cohort analysis (n=7810) measuring STI incidence (syphilis, gonorrhoea and chlamydia) as well as incare viral load (ICVL) and percentage with all viral loads less than the limit of detection (%<LLOD) by year (2012–2016) among those with incident STIs. Results: From 2012 to 2016, the incidence of STIs increased: chlamydia from 2.1 to 3.4 cases/100 person-years (p=0.0006), gonorrhoea from 2.1 to 4.0 (p<0.0001), syphilis from 1.7 to 2.6 (p=0.0042) and any STI episode from 5.3 to 8.8 (p<0.0001). STI incidence rates increased for those aged 18–34 (from 13.2 to 23.2 cases/100 person-years, p<0.0001), cisgender men (from 6.5 to 11.5, p<0.0001), non-Hispanic whites (from 8.6 to 16.1, p=0.0003) and men who have sex with men (from 9.3 to 15.7, p<0.0001). During 2012–2016, the ICVL among those with incident STIs improved from 108 to 19 copies/mL and %<LLOD from 23.6% to 55.1%. However, even in 2016, younger participants, cisgender and transgender women, non-Hispanic blacks and Hispanics had higher ICVLs and lower %<LLOD. Conclusions: Rates of incident STIs rose among persons in care for HIV in Washington, DC, with improved but not optimal measures of HIV viral suppression. These findings inform focused interventions towards preventing STI transmission and ending the HIV epidemic.